Politeness Strategies Used in Ellen DeGeneres’s TV Talk Show with Barack Obama as the Guest Star - Eni Dharmayanti, Ni Kadek; Sukarini, Ni Wayan; Weddha Savitri, Putu (Humanis; Vol 22 No 1 (2018), 2018)
This undergraduate thesis is entitled Politeness Strategies Used in Ellen DeGeneres’s TV Talk Show with Barack Obama as the Guest Star. Ellen DeGeneres is an American comedian, television host, actress, writer, and producer. The aims of this study are to analyze the type of politeness strategies used in Ellen DeGeneres’s talk show script with Barack Obama as the guest star, and to identify the factors influence the choice of strategies.The data in this study were obtained from a talk show entitled Ellen DeGeneres. The process of collecting data was done through documentation method. The theories applied to support this study are theory proposed by Brown and Levinson (1978) used to analyze the types of politeness strategies, and also the same theories used to identify the factors influence the choice of strategy. The sentences which were used as the data were the sentences of the conversation applied the politeness strategy in script. Politeness strategies and the factors that influence the choice of strategies have a close connection to each other, whether when the speakers talks to female or male, have different social status, have a close relationship, or they always try to act politely in every situations. In two episodes of Ellen DeGeneres talk show with Barack Obama as the guest star the politeness strategy mostly applied in the positive politeness strategy. It also has the connection with the factor influence the choice of strategy.